Eco-Friendly and Highly Efficient Multigram Synthesis of N-(2- Hydroxyethyl)-2-Oxo-2H-Chromene-3-Carboxamide as a Useful Intermediate Using Sonochemistry - da Silveira Pinto, Ligia S.; de Souza, Marcus V. N. (Current Green Chemistry, 2018)
This study describes a new, simple and efficient process for the preparation of N-(2- hydroxyethyl)-2-oxo-2H-chromene-3-carboxamide, on a multigram scale (0.38 moles), by using ultrasound irradiation as green chemistry method. Optimal conditions and yield (83%) were obtained by using 1.2 molar equivalents of ethanolamine at 675 W for 5.0 hours. This intermediate is very versatile and could be transformed in a wide range of derivatives, which could be employed in different areas, such as inorganic complexes, dyes, pesticides and fluorescent coumarins. In the medicinal chemistry, N-(2-hydroxyethyl)-2-oxo-2H-chromene-3-carboxamide is also very useful because a wide variety of compounds could be synthesized and evaluated with diverse types of diseases. In this context, it can be mentioned N-(2-chloroethyl)-2-oxo-2H-chromene-3-carboxamide, a useful intermediate, which was synthesized in this work in gram scale (0.04 moles) in 80% of yield, that could react with diverse types of nucleophiles.
Keywords: coumarin